Reframing Cerebral Malaria Therapy through Blood-Brain Barrier Repair and Neuroprotection: A Systematic Review of Adjunctive Strategies - Kis Djamiatun (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Cerebral malaria is a severe complication of Plasmodium falciparum infection that can cause coma, death, and persistent neurological impairment despite effective antimalarial treatment. Blood–brain barrier disruption, endothelial dysfunction, inflammation, hypoxia, oxidative stress, and neurovascular injury are central to its pathogenesis. This review evaluated current evidence on adjunctive strategies targeting blood–brain barrier repair and neuroprotection in cerebral malaria. Methods: This systematic review followed PRISMA 2020 guidelines. PubMed and Scopus were searched for studies published between January 1, 2015 and April 30, 2026. Eligible studies included human, animal, and experimental investigations of cerebral malaria reporting adjunctive therapy outcomes related to blood–brain barrier integrity, endothelial activation, neurovascular injury, neurological outcomes, or survival. Data were extracted using a standardized approach and synthesized narratively because of substantial heterogeneity; meta-analysis was not performed. Results: Twenty-two studies met the inclusion criteria. Blood–brain barrier disruption was linked to interacting mechanisms involving parasite sequestration, cytoadherence, endothelial activation, inflammation, hypoxia, oxidative stress, nitric oxide dysregulation, metabolic disturbance, and impaired cerebral microcirculation. Several adjunctive interventions improved blood–brain barrier integrity, reduced vascular leakage, attenuated neuroinflammation, or limited neurovascular injury in experimental models. However, most evidence remained preclinical, and standardized neurovascular endpoints, biomarker-guided stratification, and long-term neurological assessments were rarely used. Conclusions: Blood–brain barrier repair and neuroprotection are important targets for adjunctive therapy in cerebral malaria. Future studies should validate these strategies in clinically relevant models and human trials using standardized endpoints, biomarkers, and long-term neurological outcome measures.